GEOTHERMAL ASPECTS OF DEVELOPMENT OF ASTHENOSPHERIC UPWELLINGS BENEATH CONTINENTAL RIFT ZONES - Zorin Y.A.; Lepina S.V. (My University, 1985)
Geophysical data indicate that beneath Late Cenozoic continental rift zones there are asthenospheric upwellings with their upper surfaces reaching the Moho at depths of 30–40 km. Under neighboring stable regions the asthenospheric surface is situated at a depth over 100 km. Evidently, rifting was causally related with the development of such upwellings.The authors performed numerical two-dimensional modellings of the formation process of the asthenospheric upwelling, assuming progressive partial melting of lithosphere. It turned out that correlation of the time period required with the time of development of Late Cenozoic rift zones (15–40 m.y.) requires the heat flow into the base of the lithosphere to be very high (200–300 mW m−2). Such values of heat flow would cause an intensive melting of the lower crust, and the composition of volcanics shows that this does not take place during the late stages of evolution of rift zones.Most probably, the asthenospheric material mechanically replaces lithosphere along weak zones: blocks are detached from the lithosphere and sink into the asthenosphere. Plastic flow in the solid part of the mantle is of secondary importance. We simulated this replacement through an upward movement of the 1200°C isotherm (temperature of mantle solidus). Deformations of the mantle and crust were neglected. Above this isotherm the temperature field in the lithosphere was computed by means of a numerical solution of the equation of energy conservation.Two-dimensional models have been constructed for rift zones of the Baikal, the Rio-Grande and the Basin and Range Province. Regional values of heat flow of these regions were successfully correlated with geophysical data on Curie depths and on the structure of the upper mantle, assuming that the asthenosphere reached the Moho some million years ago and the crust is still being heated on a regional scale. These estimates of time are in good agreement with the beginning of the stage of most rapid rifting in these zones. With such models it is not difficult to reconcile the total time for the development of the asthenospheric upwellings with the observed duration of rifting.In the rift zones mentioned above, crustal cooling is possible only on individual narrow segments with local anomalies of heat flow which may be produced by basalt dikes situated at comparatively small depths.
Keywords: Cenozoic; Cenozoic; Кайнозой